Influences of visual attributes of food packaging on consumer preference and associations with taste and healthiness - Marques da Rosa, V; Spence, C; Miletto Tonetto, L (Wiley, 2018)
Two experiments designed to investigate how the shape and colour of packaging, and product category, conjointly impact consumers’ product and packaging expectations are reported. In Experiment 1, the shape (rounded vs. angular) and visual appearance (greyscale, red‐to‐yellow and blue‐to‐green colour schemes) of the packaging were manipulated. Dependent measures were preference (willingness to purchase the product, how attention‐capturing the packaging is, and the pleasantness of the design) and any taste associations. In Experiment 2, shape (rounded vs. angular), colour (red‐to‐yellow vs. blue‐to‐green colour schemes), and product category (buttery vs. cereal cookies) were manipulated. In this case, the dependent measures were the perceived product healthiness and the preference of consumers. The results of Experiment 1 revealed that packaging colour influenced product preference. Red‐to‐yellow and blue‐to‐green colour schemes and angular packaging were preferred over greyscale and round packaging. Colour also influenced taste associations, while shape only influenced ratings of expected sweetness. In Experiment 2, packaging shape and product category influenced product preference. In particular, rounded packaging and the packaging of buttery cookies were preferred over angular packaging and the cereal cookies packaging. The healthiness of the product was rated higher for the rounded and red‐to‐yellow packaging containing a buttery product. Taken together, these results highlight the important role played by colour, shape, and category on the expectations and associations elicited by viewing product packaging.